2012
DOI: 10.2151/jmsj.2012-a03
|View full text |Cite
|
Sign up to set email alerts
|

Projections of Future Changes in Precipitation and the Vertical Structure of the Frontal Zone during the Baiu Season in the Vicinity of Japan Using a 5-km-mesh Regional Climate Model

Abstract: Future changes in precipitation and the vertical structure of the frontal zone around Japan during the Baiu season are investigated using regional climate experiments with a 5-km-mesh non-hydrostatic model, driven for the present-day and future climates by output from global warming experiments using a 20-km-mesh atmospheric global circulation model under the SRES-A1B scenario.Significant increases are projected for the future climate relative to the present-day in daily precipitation amounts around western … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 38 publications
4
25
0
Order By: Relevance
“…Sato and Takahashi (2001) and Inoue and Matsumoto (2006) reported that the northward migration of the Baiu front slows down in the late Baiu season. Interestingly, these observed changes are consistent with future changes predicted by high-resolution models under a scenario of global warming (Kusunoki et al 2011;Kanada et al 2012). In addition, Kanada et al (2012) reported that the delay in the northward migration of the Baiu front may result in substantial increases in the amount of precipitation and in a southward shift of the mean location of the Baiu front from 33.5°N to 33.0°N during the late Baiu season.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…Sato and Takahashi (2001) and Inoue and Matsumoto (2006) reported that the northward migration of the Baiu front slows down in the late Baiu season. Interestingly, these observed changes are consistent with future changes predicted by high-resolution models under a scenario of global warming (Kusunoki et al 2011;Kanada et al 2012). In addition, Kanada et al (2012) reported that the delay in the northward migration of the Baiu front may result in substantial increases in the amount of precipitation and in a southward shift of the mean location of the Baiu front from 33.5°N to 33.0°N during the late Baiu season.…”
Section: Introductionsupporting
confidence: 82%
“…Previous studies have used the location of the largest north-south gradient of θ e in the lower atmosphere to define the BFZ (Tomita et al 2011;Kanada et al 2012). We therefore find the location of the BFZ using the vertically averaged (925−850 hPa) equivalent potential temperature áθ e ñ in central Japan (132°E−137°E).…”
Section: Identification Of the Bfzmentioning
confidence: 99%
“…2a). At the center of this rainband, θ e in the lower atmosphere is around 335 K and θ e gradually decreases (increases) toward the north (south; Tomita et al, 2011;Kanada et al, 2012). In this study, we calculated the vertically averaged (925-850 hPa) equivalent potential temperature θ e around the observation site, and then the summer precipitation was divided into warm and cold events depending on the θ e of the air mass-induced precipitation.…”
Section: Precipitation Classificationmentioning
confidence: 99%
“…In the KAKUSHIN Program (Kitoh et al 2009), Kanada et al (2012) discovered an increase of extreme precipitation in early July in the future climate by analyzing a 5-km-mesh non-hydrostatic regional climate model (NHRCM05) under the A1B scenario proposed in IPCC Special Report on Emission Scenarios (SRES;IPCC 2000). Nested in an outer 20-km-mesh global atmospheric climate model (AGCM20), NHRCM05 outputs 30-minutes precipitation.…”
Section: Introductionmentioning
confidence: 99%